The impact of the economic blockade on education in Iraq during the period (1990-2003) - Al-Jailawi, Prof. Dr. Inas Hamza Mahdi Al-Jailawi; Mahdi, Dr. Sahar Abdul Salam Mahdi (Sulaimani Journal for Humanities, 2026)
The research deals with the impact of the economic blockade on education in Iraq during the period 1990-2003, The research pointed out the most important reasons and motives for imposing economic sanctions on Iraq, and the impact of that on the education system, and the extent of its decline and deterioration as a result of those sanctions. The research included three research axes. The first axis was an introduction to the reasons and motives for the economic blockade on Iraq, while the second and third axes dealt with the conditions of education in Iraq during the years of the economic blockade. The research relied on many diverse sources, including foreign and Arab sources, in addition to foreign newspapers, which enriched the research with useful information.
Keywords: Education; economic blockade; primary and secondary education